Superior Oblique Anterior Transposition with Horizontal Recti Recession-Resection for Total Third-Nerve Palsy - ÇERMAN, EREN; ERASLAN, MUHSİN (HINDAWI LTD, 2015)
Aims. To report the results of lateral rectus muscle recession, medial rectus muscle resection, and superior oblique muscle transposition in the restoration and maintenance of ocular alignment in primary position for patients with total third-nerve palsy. Methods. The medical records of patients who underwent surgery between March 2007 and September 2011 for total third-nerve palsy were reviewed. All patients underwent a preoperative assessment, including a detailed ophthalmologic examination. Results. A total of 6 patients (age range, 14-45 years) were included. The median preoperative horizontal deviation was 67.5 Prism Diopter (PD) (interquartile range [IQR] 57.5-70) and vertical deviation was 13.5 PD (IQR 10-20). The median postoperative horizontal residual exodeviation was 8.0 PD (IQR 1-16), and the vertical deviation was 0 PD (IQR 0-4). The median correction of hypotropia following superior oblique transposition was 13.5 +/- 2.9 PD (range, 10-16). All cases were vertically aligned within 5 PD. Four of the six cases were aligned within 10 PD of the horizontal deviation. Adduction and head posture were improved in all patients. All patients gained new area of binocular single vision in the primary position after the operation. Conclusion. Lateral rectus recession, medial rectus resection, and superior oblique transposition may be used to achieve satisfactory cosmetic and functional results in total third-nerve palsy.
Keywords: OCULOMOTOR NERVE PALSY; SURGICAL-MANAGEMENT; 3RD; STRABISMUS; EXOTROPIA; SURGERY